Freedom of press: newspaper reporting in relation to printing presses and publications act 1984 / Batul Sabbir, Noor Nadira Noordin, Aizuddin Arshad - Sabbir, Batul; Noordin, Noor Nadira; Arshad, Aizuddin (2006)
Freedom of press is a branch of freedom of speech and expression enshrined in Article 10(l)(a) of the Federal Constitution. Although embodied in the Constitution the practice of it has been ambiguous to media practitioners, the newspaper journalists in particular. Furthermore, the laws regulating the media are aplenty and as such it is bound for confusion to occur. This research concentrates on the Printing Presses and Publications Act 1984 as one of the major laws governing the media fraternity. The Act grants absolute power to the Minister concerned to revoke, suspend a licence and permit given to the newspaper companies. Moreover, the decision made by the Minister is final and conclusive, as such even the court could not intervene and review the decision. The motive of the project paper is to shed light on the possibility of abuse of power on the part of the Minister in granting, revoking and suspending the licence and permit of any newspaper companies. In addition, this research is aimed to probe on whether the general public believes that the media should be given more elbow room to perform their obligations towards the public in informing truthful reports. In granting more freedom to the editors and journalist alike, the issue of self-regulation is a matter that needs to be addressed. The significance of the research is to provide an alternative to the current state of affairs with regard to newspaper reporting. Concurrently, it is also hoped that the severity of the Printing Presses and Publications Act 1984 would be dealt with particularly on the issue of discretionary power of Minister in issuance of licence and permit.